Metastasising ameloblastoma or ameloblastic carcinoma? A case report with mutation analyses - Pavel Hurník; Barbora Moldovan Putnová; Tereza Ševčíková; Eva Hrubá; Iveta Putnová; Josef Škarda; Martin Havel; Oldřich Res; Jakub Cvek; Marcela Buchtová; Jan Štembírek (BMC, 2023)
Abstract Background Ameloblastic carcinoma and metastasising ameloblastoma are rare epithelial odontogenic tumours with aggressive features. Distinguishing between these two lesions is often clinically difficult but necessary to predict tumour behaviour or to plan future therapy. Here, we provide a brief review of the literature available on these two types of lesions and present a new case report of a young man with an ameloblastoma displaying metastatic features. We also use this case to illustrate the similarities and differences between these two types of tumours and the difficulties of their differential diagnosis. Case presentation Our histopathological analyses uncovered a metastasising tumour with features of ameloblastic carcinoma, which developed from the ameloblastoma. We profiled the gene expression of Wnt pathway members in ameloblastoma sample of this patient, because multiple molecules of this pathway are involved in the establishing of cell polarity, cell migration or for epithelial-mesenchymal transition during tumour metastasis to evaluate features of tumor behaviour. Indeed, we found upregulation of several cell migration-related genes in our patient. Moreover, we uncovered somatic mutation BRAF p.V600E with known pathological role in cancerogenesis and germline heterozygous FANCA p.S858R mutation, whose interpretation in this context has not been discussed yet. Conclusions In conclusion, we have uncovered a unique case of ameloblastic carcinoma associated with an alteration of Wnt signalling and the presence of BRAF mutation. Development of harmful state of our patient might be also supported by the germline mutation in one FANCA allele, however this has to be confirmed by further analyses.